The effects of holding space on growth and survival of individually-reared three-spot crab (Portunus sanguinolentus) - Nicholson, Stephen; Mann, D.; Fotedar, Ravi; Paterson, B. (Blackwell Publication, 2008)
The problem of cannibalism in communally reared crabs can be eliminated by separating the growing crabs into holding compartments. There is currently no information on optimal compartment size for growing crabs individually. 136 second instar crablets (Portunus sanguinolentus) (C2 ca. 7–10 mm carapace width (CW)) were grown for 90 days in 10 different-sized opaque and transparent walled acrylic compartments. The base area for each compartment ranged from small (32 mm x 32 mm) to large (176 mm x 176 mm). Effects of holding space and wall transparency on survival, CW, moult increment, intermoult period and average weekly gain (AWG) were examined. Most crabs reached instars C9–C10 (50–70 mm CW) by the end of experiment. The final survival rate in the smallest compartment was 25% mainly due to moult-related mortality predominantly occurring at the C9 instar. However, crabs in these smaller compartments had earlier produced significantly larger moult increments from instar to instar than those in the larger compartments (P < 0.05). Crabs in the smaller compartments (<65 mm x 65 mm) also showed significantly longer moult periods (P < 0.05). The net result was that AWG in CW was 5.22 mm week ︡1 1 for the largest compartment and 5.15 mm week︠1 in smallest and did not differ significantly between compartment size groups (P = 0.916). Wall transparency had no impact on survival (P = 0.530) but a slight impact on AWG (P = 0.014). Survival rate was the best indicator of minimumacceptable compartment size (43 mm x 43 mm) for C10 crablets because below this size death occurred before growth rate was significantly affected. For further growth, it would be necessary to transfer the crablets to larger compartments.